Rebeliões em Santiago de Compostela: movimentos urbanos e exclusão socioespacial no século XII - Viçose, Jordano (2023)
This doctorate degree thesis analyzes the two rebellions from Santiago de Compostela occurred during the Diego Gelmírez (1101-1140) episcopate that came from the Human Geography teachings, particularly, from “fixed and flows” theory by Milton Santos (1926-2001). The fixed and flows, installed or that cross Santiago de Compostela in the transition of the XI century to XII turned it into one of the most importants pilgrimage centers of Christianity, however, broke up with the Jacobeans traditions and banned great part of the native population from their own city. Through the study of Historia Compostelana, the only textual source which deals with insurrection through narrative analysis as a methodological technique to data survey, we defend that the exaltation policy of the see of Compostela was the neuralgic cause of upheavals. Beginning under the bishopric of Diego Peláez (1071-1088), such policy consisted (I) in the construction of the romantic basilica of Santiago; (II) in legitimation that the mortal remains of the apostle James lay in Galiza; (III) encouraging pilgrimages to jacobean shrine; and (IV) in the liturgical-ecclesiastical reform of the church of Compostela. By promoting and directing transformations in the city space system Diego Gelmírez engendered deep dissatisfaction among people from Compostela. The preference given to the transitory public and the foreign customs to the detriment of native population and local customs motivated the urban movements of 1116-1117 and 1136. The temporal proximity between them – about twenty years - and the significant similarity between these rebellions, including from the point of view of the order of events indicate that people from Compostela continued to be excluded from a space constituted to reproduce the pilgrimage ritual and reinforce the lordly-episcopal power.